Implementation of a New and Modified Scheme of Butler Matrix for C-Band Applications with Enhanced Characteristics - Maleki, Mostafa; Nourinia, Javad; Ghobadi, Changiz; Naderali, Rahim (Společnost pro radioelektronické inženýrství, 2020)
In this paper, the structure of a miniaturized broadband 4 × 4 Butler matrix is presented. All components of the proposed feeding network are designed in a way that they have the smallest electrical size and acceptable performance in the C band. Despite conventional Butler matrix consists of phase shifters, the proposed network benefits from dummy crossover, which leads to improving the phase difference bandwidth. Since in beam switching networks, 90° coupler has a vital role, the main focus is concentrated on the aforementioned component as mentioned above. The compactness of the proposed coupler is associated with embedding the S-shaped arms instead of ordinary elements. Due to overcoming the problem of a mismatch phase difference between phase shifter and crossover, the modified dummy crossover is used. In order to improve the overall performance of the depicted feeding network, S-shaped electromagnetic bandgap structures are used between elements. They reduce destructive mutual coupling effect hence leads to enhance total network efficiency. The extracted results determine that the bandwidth of the presented network is from 3.5 ~ 8.2 GHz that covers the C band totally.
Keywords: Butler matrix; coupler; broadband; electromagnetic band gap